The epidemiology of skin cancer at Dr. Cipto Mangunkusumo National Central General Hospital from 2014 to 2017 - Wibawa, Larisa Paramitha; Andardewi, Melody Febriana; Kristanti, Inge Adi; Arisanty, Riesye (UI Scholars Hub, 2019)
Background: The incidence of skin cancer has been increasing over the past decades globally. At present, there is no valid national cancer data in Indonesia. The purpose of this study is to evaluate the increment of skin cancer cases at Dr. Cipto Mangunkusumo National General Hospital, Jakarta. Methods: In this retrospective descriptive study, we evaluated all pigmented skin tumor cases from June 2014 to June 2017. Data were obtained from the Department of Anatomical Pathology and medical records at Dr. Cipto Mangunkusumo National General Hospital. Data were compared with previous reports. Results: From 263 skin cancer cases, the most frequent skin cancer was basal cell carcinoma (BCC; 66.9%), followed by squamous cell carcinoma (SCC; 27.4%), and malignant melanoma (MM; 5.7%). Most of the skin cancer were predominantly in the female population. In BCC and SCC, most of the patients were within the age group above 60 years (n = 106 and 18, respectively). In MM, the incidence is greater in age group of 41–50 years (n = 5). For BCC and SCC, the distribution sites of lesions were mostly in sun-exposed areas, whereas the distribution sites of MM were mostly in non-sun-exposed areas. Median diameters of BCC, SCC, and MM were 2, 4, and 6.5 cm, respectively. There was an increase of BCC incidence from 1996 to 2017. Conclusion: In comparison with other types, the incidence of BCC in Dr. Cipto Mangunkusumo National General Hospital is increasing. A well-documented skin cancer registry is required to establish national data of skin cancer in Indonesia.